PENERAPAN TEKNOLOGI PERTANIAN SEBAGAI UPAYA PEMBERDAYAAN KETERAMPILAN KERJA WARGA BINAAN PEMASYARAKATAN DI LAPAS KELAS III DHARMASRAYA - Adi Surya, Ridho; Rahmat, Diding (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN, 2024)
Correctional Institutions (LAPAS) are part of the Ministry of Law and Human Rights which have the responsibility to carry out the main tasks of the Ministry in the field of placement, care and services for prisoners. One example of a prison is the Class III Dharmasraya Correctional Institution, a correctional institution located in Dharmasraya Regency, West Sumatra Province. Inmates or prisoners serving a sentence at the Class III Dharmasraya Penitentiary have a need to develop skills during their prison period. One of the skills that is very suitable for development by inmates is the application of agricultural technology. This program aims to achieve two main benefits: first, encouraging the motivation of inmates to become entrepreneurs after being released from prison, so as to improve their economy; second, increase their knowledge about the application of good agricultural technology. In this empowerment activity, training and direct practice methods are used. The result of this empowerment program is an increase in the group's knowledge and skills in applying agricultural technology in carrying out farming effectively.